The Use of the Health Booklet/Prenatal Record and Women's Satisfaction with the Prenatal Care in Nampula, Mozambique - Reis-Muleva , Belarmina (2025)
Introduction: Prenatal care plays a crucial role in promoting maternal and fetal health, and women’s health records, in their proper use, are a tool for improving maternal and child health. Therefore, it is necessary to consider women’s satisfaction with prenatal care. Objectives: (1) To verify the use of the woman’s health booklet/prenatal record and (2) describe women’s satisfaction with prenatal care. Method: A quantitative, cross-sectional, descriptive study conducted in Nampula, Mozambique, with 339 women aged 18 to 49 years, interviewed using a structured instrument in Google Forms, which was pre-tested and applied with a tablet. The use of the booklet was evaluated based on the prenatal care information recorded on prenatal and the women’s satisfaction with prenatal care was assessed using the Patient Expectations and Satisfaction with Prenatal Care Scale. Results: 393 women were approached, but 54 of them (13.7%) were not carrying their health record booklet. Of the 339 women interviewed, 50.7% of them had records of four or more prenatal visits; 57.8% of them had records of syphilis testing; and 64.3% of blood pressure measurement. There was also a low percentage of records for urine tests, complete vaccination schedules, and blood counts. In terms of satisfaction, more than half of the women were dissatisfied with the waiting time to be seen by a health professional. Conclusion: The low number of entries in women's health records and the dissatisfaction with prenatal care highlight the need to train professionals and raise awareness among women.